IMPLEMENTATION OF QUR'AN LITERATURE ON ISLAMIC EDUCATION IN THE DIGITAL ERA - Irham Miftakhul Jannah; Lestari, Risma Rahajeng; Zakiyah, Lus Firdaus (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2021)
The achievement of the goals of Islamic education in the digitalization era has not yet reached the peak of proper realization. The effect of digitalization is devenitive, meaning it saves Muslims from all the pollution and destruction caused by Western ideas that come through various disciplines that can threaten traditional Islamic moral standards. Thus, the purpose of this research is to boost the morale of a nation's children by implementing al-Qur'an literacy through qualitative-descriptive methods. It can answer a research, namely al-Qur'an literacy as a forum for moral education of the nation's children by developing advanced technology in the digital era by mastery of reading verses of the Al Qur’an through digital platforms.